Breast reconstruction following mastectomy - Tepavicharova, P (Acta chirurgiae plasticae, 1990)
Immediate reconstruction contributing to prompt elimination of the postmastectomy psychological sequelae, and not interfering with the postoperative adjuvant treatment, is recommended in clinical stages T1, 2N1M0 patients. Delayed reconstruction is recommended in the other clinical stages, and in tumors located in the inner quadrants. In case of limited peritumoral tissue excision the reconstruction is effected by simple techniques with expanders and implants. In case of extensive peritumoral tissue removal myocutaneous flaps have to be used. The methods of breast and nipple-areola reconstruction should be considered with a reference to the individual requirements of the patient and the experience of the surgeon.
Keywords: Breast; plastická chirurgie; Mastectomy; reoperace; prsy; Middle Aged; Surgery, Plastic; Adult; Reoperation; ženské pohlaví; Surgical Flaps; Humans; lidé středního věku; chirurgické laloky; dospělí; Prostheses and Implants; Female; mastektomie; lidé; protézy a implantáty